Effects of the variety and content of coal gangue coarse aggregate on the mechanical properties of concrete. (30th September 2019) - Zhou, Mei; Dou, Yanwei; Zhang, Yuzhuo; Zhang, Yuanqiang; Zhang, Boqun
Highlights: The macro and micro characteristics of coal gangue and natural gravel are analyzed. The failure modes of concrete with different coal gangue aggregates are revealed. The relationship between microstructure and macrobehavior of concrete is described. The stress-strain curve model of concrete with different aggregates is established. Abstract: Concrete were prepared by replacing natural gravel (N) with spontaneous combustion gangue (S) or rock gangue (R) at intervals of 25%. Mechanical tests were carried out and the microstructural features of the concrete were characterized. Failure modes and strength of different concrete are various, and the compressive strength of the concrete meets the design requirements of C30 strength grade concrete. The axial compression failure mode of R coarse aggregate concrete (RAC) was shear failure. As the S replacement percentage increased, the axial compression failure mode of S coarse aggregate concrete (SAC) transformed from shear failure to longitudinal splitting failure. The ITZ of SAC is the best; as the replacement percentage increased, the peak stress and slope of the rising section of the stress-strain curves of RAC and SAC decreased, and the peak strains increased. Finally, compressive stress-strain curve prediction models for coal gangue coarse aggregate concrete were suggested.